Anorthosltes and Gabbroic Bodies In Northern Cape Breton Island, Nova Scotia - Dupuy, C.; Dostal, J.; Smith, P.; Kepple, J. (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 1986)
Several leneoldal arorthosltlc bodies of probable Precaabrian aga, are swosed In northern Cape Breton Island within a central fault-banded block of quartzofeldspathlc (pelsses. One of these, the Red River anorthoslts coaplex Cell ka long and up to 1 ka Hide) ranges free anorthoslte to anorthositlc gabbro with hltfi Aljpa and Sr contents and large positive Eu anoaalles resulting aalnly froa plagloolase aocuailatlon. Following an episode of polyphase deforaatlon and aaphlbollte facles aetaaorphlsa, a aonzodlorite-gabbro body of unknown age was Intruded Into both the anorthoslte and Its host rocks. The gsochealstry of this Intrusion Indicates that It Is calc-alkallne. Granite sheets, Intrusive Into the aonzodlorlte-gabbro body, do not appear to be coaagaatlc based upon the trace eleeent chealstry. These sheets aay be correlated with granitic plutons in the Cape North area which have been dated at 330 ±23 to.